Sliding wear of silicon carbide modified by etching with chlorine at various temperatures - Choi, H. -J.; Bae, H. -T.; Lee, J. -K.; Na, B. -C.; McNallan, M. J.; Lim, D. -S. (ELSEVIER SCIENCE SA, 2009)
The effect of reaction temperature on the formation of a carbon layer on the surface of SiC has been investigated. Subsequently, the tribological properties of the formed carbon layers were studied. The experimental procedure involved exposing reaction-bonded SiC balls to a flowing gas mixture of 5% Cl-2, 2.5% H-2, and At at a high temperature of 800, 1000, or 1200 degrees C. A ball-on disk tribometer was used to investigate the friction and wear behavior of the treated specimens. While partially unreacted SiC phases were observed in the layer modified at 800 degrees C, rhombohedral graphite crystals were formed in the layer modified at 1200 degrees C. Compared to untreated SiC, the treated SiC materials were found to have relatively low friction coefficients and better wear resistance. Increasing the treatment temperature was found to improve the tribological performance of the resulting surface-modified Sic balls. A possible reason for this tribological improvement has been discussed based on the observed carbon phases. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: DIAMOND-LIKE CARBON; TRIBOLOGY; COATINGS